MINI REVIEW: PERBANDINGAN KINERJA ELEKTRODA SELEKTIF ION Cu2+ DENGAN BERBAGAI IONOFOR DALAM MATRIKS PVC-DOP - Safira Qisthina Wardhana; Alimuddin; Moh Syaiful Arif (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Copper (Cu) contamination resulting from industrial waste can have detrimental effects on both the environment and human health. To control Cu pollution, a rapid and accurate detection method is required. This study compares the performance of Cu²⁺ ion-selective electrodes using various ionophores in a polyvinyl chloride (PVC) matrix plasticized with dioctyl phthalate (DOP). The ionophores compared include EDTA, Rhodamine 6G, and Schiff base. The evaluated parameters include Nernstian slope, detection limit, linear range, response time, and selectivity. The results indicate that Rhodamine 6G and Schiff base exhibit superior sensitivity and response time, while EDTA provides better long-term stability. Keywords: Ion Selective Electrode, Cu2+ metal, Ionophore